Are Adewale and Ngochi more employable than Jamal and Lakeisha? The influence of nationality and ethnicity cues on employment-related evaluations of Blacks in the United States. Issue 4 (3rd July 2020) - Howard, Simon; Borgella, Alex M.
ABSTRACT: Previous research has consistently shown that racial bias can influence employers' perceptions and evaluations of Black individuals in hiring and promotion decisions. However, within-race differences (e.g., skin tone, Afrocentric features) can lead to variation in these decisions. In addition to phenotypical variation, ethnicity cues (e.g., perceived country of origin, name) may be important within-race factors influencing the perception and evaluations of Black job applicants. Using a resume evaluation paradigm, participants evaluated one of three resumes in which the target applicant's name provided cues about ethnicity (either Black American, Black African, or White American). Results suggest that Black Americans may experience more discrimination in hiring and are generally perceived less positively across several employment-related domains than both White and Black African applicants. Specifically, we find that Black Americans are less likely to be selected for an interview or offered a job and are evaluated more negatively overall relative to Black Africans.